PHOTOINHIBITION INDUCED ALTERATIONS IN PHOTOSYNTHETIC ELECTRON TRANSPORT ACTIVITIES OF THE CYANOBACTERIUM SYNECHOCOCCUS 6301 - Y. S. S. CHANDRA SEKHAR; P. BRAHMAJI RAO; M. AYYA RAJU (The Bioscan, 2011)
In this investigation an attempt has been made to study the highlight (Photoinhibition) induced alterations in the cyanobacterium Synechococcus 6301. The electron transport activities have been measured using oxygen electrode with spheroplasts of the intact cells using artificial electron donors, accepters and inhibitors. They indicate that whole chain and photosystem II catalyzed electron transport activities are more sensitive to high light (410 - 620 Wm-2) when compare to that of photosystem I. Light intensity measurements (420 - 15 Wm-2) gave clear indications that the energy transfer from phycobilisomes to photosystem II reaction centre is major target since the inhibition at light saturating conditions than at light limiting conditions.